Identifikasi Faktor Perubahan Status Gizi Anak Balita Indonesia - Noviati Fuada (Poltekkes Kemenkes Semarang, 2015)
The objective of this research is to identify the differentiating factor of nutrition statuses of the double burden in the children under five. The method applied is Cross-sectional design. The sample data for Analisys data with Aggregate Susenas (2007 and 2010 ), Riskesdas (2007 and 2010). Unit analysis is the province. Statistical analysis using discrimination.The results show that differentiating factor in the demographic transition is the delta of proportion of demographic dependency ratio variable. In economic transition is the delta of proportion of poor household’s variable. In social transition is the delta of proportion of Elementary Education variable, in food sufficiency transition, is protein adequacy for household variable. All of them, the determinants factor, is dependency ratio variable. When assuming from the other factors is invariable, it is predicted if any a demographic bonus case, also any double burden problem. The conclusions is differentiating factor of areas that experienced double burden and that are not, is the delta of proportion dependency ratio variable.